A review of the genus Spanagonicus Berg (Hemiptera: Miridae: Phylinae: Nasocorini) with the description of novel antennal characters, the description of a new species from Central America, and a key to currently known taxa - Menard, Katrina L. (Zootaxa, 2015)
The New World genus Spanagonicus Berg, 1883 is reviewed. A new species, Spanagonicus schusterus sp. nov. is described from Central America. A key to all known species, as well as redescriptions for all species but S. tiquiensis Carvalho & Carpintero (which was unavailable for inspection), are provided. Characterization of the sexual dimorphism, morphology, and possible function of the newly discovered spatulate setae on the ventral surface of male antennae is also discussed. Color digital habitus images and genitalic illustrations are provided for both male and female specimens of Spanagonicus. Scanning electron and transmission electron micrographs of the second antennal segment of male and female specimens of S. albofasciatus are also included.